88.1k views
4 votes
What is -5(4x + 3) = -5x - 5 - 15x - 10?

User Xavi
by
4.9k points

2 Answers

4 votes

Answer:

Infinite Solutions

Explanation:

Firstly we distribute

-20x - 15 = -5x - 5 - 15x - 10

Collect like terms

-20x - 15 = -20x - 15

This represents infinite solution because they will result in 0.

User Mmond
by
4.6k points
4 votes

Answer:

Explanation:

-5(4x + 3) = -5x - 5 - 15x - 10

-5*4x - 5*3 = -5x - 5 - 15x - 10

-20x - 15 = -5x - 5 - 15x - 10

-20x + 5x + 15x = -5 -10 - 15

0= 0

User Marc Edwards
by
4.8k points